The One Anastomosis Gastric Bypass Is a Suitable Alternative to Roux-en-Y Gastric Bypass in Patients with Body Mass Index ≥50 kg/m2: A Propensity Score-Matched Analysis - Lindsy van der Laan; Dionne Sizoo; Loek J.M. de Heide; André P. van Beek; Marloes Emous (Obesity Facts)
Introduction: Body mass index (BMI) ≥50 kg/m2 is more challenging for the metabolic bariatric surgeon because of a thicker abdominal wall, more visceral fat, and hepatomegaly by liver steatosis. This study aimed to give an overview of 5-year outcomes after one anastomosis gastric bypass (OAGB) and Roux-en-Y gastric bypass (RYGB) in these patients in terms of weight loss, remission of comorbidities, and complications. Methods: This retrospective single-center cohort study focused on patients with BMI ≥50 kg/m2 undergoing OAGB or RYGB between 2015 and 2017 at a nonacademic teaching hospital in the Netherlands. A 1:1 propensity score-matched (PSM) comparison was conducted. Results: In total, 158 patients underwent OAGB and 32 patients RYGB. After performing a 1:1 PSM, we obtained two nearly identical cohorts of 28 patients. Follow-up data after 5 years were available in 79% of the patients after OAGB and 82% of the patients after RYGB. Both procedures resulted in equal weight loss, remission of comorbidities, and short-term complications. More minor midterm complications were seen after OAGB (50% versus 18%; p = 0.011) due to reflux complaints (50% versus 7%; p < 0.001). The number of patients with major midterm complications did not differ (7% after OAGB versus 14% after RYGB; p = 0.388). The only major complication after OAGB was conversion to RYGB due to reflux in 7.1% of the patients. In contrast, major complications following RYGB were more diverse. Conclusion: Both procedures resulted in similar weight loss, remission of comorbidities, short-term and major midterm complications, making OAGB a suitable alternative to RYGB for patients with a BMI ≥50 kg/m2.